Virtual Conciliation and Mediation Hearings: A Systematic Review - Alves, André Luiz; Lunardi, Fabrício Castagna; Correia, Pedro Miguel Alves Ribeiro (Review of European and Comparative Law, 2025)
This article aims to conduct a systematic review on virtual conciliation and mediation hearings to identify their strengths, weaknesses, and areas for concern. The study employs a systematic review methodology, allowing for the identification, selection, analysis, and synthesis of relevant academic works. The research is directly linked to digital judicial governance, examining its dimensions in terms of accessibility, resources, structure, and judicial performance. By reviewing and analyzing the scientific studies available on Scopus, Web of Science, HeinOnline and Google Scholar databases, this study identifies recurring analytical dimensions and provides a framework that can serve as a basis for future research, contributing to the advancement of this area of knowledge.